Bioturbation by black soldier fly larvae-Rapid soil formation with burial of ceramic artifacts. - Juan M Orozco-Ortiz; Sara L Bauke; Christian Borgemeister; Eva Lehndorff; Wulf Amelung (PLoS ONE, 2021)
Bioturbation involves the incorporation of residues from the surface soil into the subsoil; however, common small soil 'bioengineers', such as earthworms or termites, are unlikely to transport human artifacts to deeper soil horizons. However, such artifacts occur in the deeper soil horizons within Amazonian Anthrosols (Terra Preta). Here we test the assumption that such tasks could be carried out by fly larvae, which could thus play a crucial role in waste decomposition and associated soil mixing under tropical conditions. We performed two greenhouse experiments with sandy substrate covered with layers of organic waste, ceramic fragments, and black soldier fly larvae (BSFL) (Hermetia illucens (L.) (Dipt.: Stratiomyidae)). We used in-situ images to assess the rate of bioturbation by BSFL, and then designed our main study to observe waste dissipation (reduction of organic carbon and phosphorus contents from waste model trials with and without charcoal) as related to larval-induced changes in soil properties. We found that the bioturbation of macroinvertebrates like BSFL was able to bury even large (> 5 cm) ceramic fragments within hours, which coincided with high soil growth rates (0.5 cm h-1). The sandy soil was subsequently heavily enriched with organic matter and phosphorus originating from organic waste. We conclude that BSFL, and possibly other fly species, are important, previously overlooked soil 'bioengineers', which may even contribute to the burial of artifacts in Anthrosols and other terrestrial waste dumps.